Procalcitonin is a Predictor for High-Grade Vesicoureteral Reflux in Children: Meta-Analysis of Individual Patient Data - Leroy, Sandrine; Romanello, Carla; Galetto-Lacour, Annick; Bouissou, Francois; Fernandez-Lopez, Anna; Smolkin, Vladislav; Chalumeau, Martin (Mosby-Elsevier, 2011)
Objective To assess the predictive value of procalcitonin, a serum inflammatory marker, in the identification of children with first urinary tract infection (UTI) who might have high-grade (>= 3) vesicoureteral reflux (VUR). Study design We conducted a meta-analysis of individual data, inCIuding all series of children aged 1 month to 4 years with a first UTI, a procalcitonin (PCT) level measurement, cystograms, and an early dimercaptosuccinic acid scan. Results Of the 152 relevant identified artiCIes, 12 studies representing 526 patients (10% with VUR >= 3) were inCIuded. PCT level was associated with VUR as a continuous (P = .001), and as a binary variable, with a 0.5 ng/mL preferred threshold (adjusted OR, 2.5; 95% CI, 1.1 to 5.4). The sensitivity of PCT >= 0.5 ng/mL was 83% (95% CI, 71 to 91) with 43% specificity rate (95% CI, 38 to 47). In the subgroup of children with a positive results on dimercaptosuccinic acid scan, PCT >= 0.5 ng/mL was also associated with high-grade VUR (adjusted OR, 4.8; 95% CI, 1.3 to 17.6). ConCIusions We confirmed that PCT is a sensitive and validated predictor strongly associated with VUR >= 3 regardless of the presence of early renal parenchymal involvement in children with a first UTI. (J Pediatr 2011;159:644-51).
Keywords: Urinary-Tract-Infection; C-Reactive Protein; Antibiotic-Prophylaxis; Acute Pyelonephritis; Serum Procalcitonin; Febrile Infants; Management; Childhood; Multicenter; Validation